Online and offline information seeking behaviours of people living with HIV in a clinic-based setting. Issue 6 (2nd September 2019) - Lwoga, Edda Tandi
Abstract : Purpose: The purpose of this study sought to determine the characteristics that distinguish online from offline information seekers among people living with human immunodeficiency virus (PLHIV) in selected regional hospitals of Tanzania. Design/methodology/approach: Questionnaire-based survey was conducted among 341 adults with human immunodeficiency virus (HIV) infection attending the HIV clinics in the regional referral hospitals in Mwanza, Mbeya and Dar es Salaam, Tanzania. The study used multivariate logistic regressions to determine factors that distinguish online HIV information seekers from offline HIV information seekers. Findings: One in every five survey participants sought online HIV information (19.6 per cent, n  = 67). Both higher level of education (odds ratio (OR) = 1.765, 95 per cent confidence interval (CI) = 1.208-2.58) and intention to use internet in future (OR = 1.566, 95 per cent CI 1.148-2.136) were predictors of online HIV information seeking behaviour at multivariate analysis. Respondents who sought online information reported to have gained knowledge such as; to understand their conditions better (77.4 per cent, n  = 41) and understand information received from health care workers (66 per cent, n  = 35), as well as acquisition of health promoting behaviour such as; asking questions during doctor's visit (55 per cent, n  = 35) and consulting a clinician when they have problems (64.3 per cent, n  = 33). The offline HIV information seekers ( n  = 274) did not use internet due to lack of information seeking skills (44.3 per cent, n  = 113) and lack of access to internet connectivity (30.2 per cent, n  = 77). Originality/value: This is a comprehensive study that differentiates online from offline HIV information seekers in the context of sub-Saharan Africa. The results suggest that interventions to improve online access information will empower patients and probably positively affect their health knowledge and health promoting behaviours.